Art and architecture of Ireland : Volume III: Sculpture 1600-2000 - Murphy, Paula; Murphy, Paula; Carpenter, Andrew; Carpenter, Andrew (Royal Irish Academy, 2015)
Introduction: Irish sculpture since 1600 -- Sculptors at work -- Biographies -- Architectural sculpture -- Architecture (Irish Georgian) and sculpture -- Arts and Crafts sculpture -- Celtic cross -- Celtic revival sculpture -- Ceramic sculpture -- Church monuments -- Churchyard and cemetery sculpture -- Classicisms -- Coins and coinage -- Collecting sculpture: private -- Collecting sculpture: public -- Competition -- Destruction and loss -- Ecclesiastical sculpture -- Education of sculptors -- Éire/Hibernia -- Exhibitions -- Famine memorial sculpture -- Foreign sculptors and their work in Ireland -- Garden sculpture -- Great exhibitions: sculpture -- Installation art -- Institute of the Sculptors of Ireland -- Irish-American sculptors -- Leitrim Sculpture Centre -- Lettering and inscriptions -- National Sculpture Factory -- Nationalist memorial sculpture -- Nude -- Painter/Sculptors -- Performance art -- Portrait sculpture -- Public sculpture -- Saint Patrick -- Sculptors' Society of Ireland -- Sculpture as situation -- Sculpture in Context -- Sculpture in the Parklands -- Statuaries and plaster shops in eighteenth-century Dublin -- Stucco- Baroque and Rococco stuccowork in Ireland -- Temporary art -- Time-based art -- War memorials -- Wayside monuments -- Wood carving -- Irish sculpture at the beginning of the twenty-first century.